Representations of in vitro fertilization in the first cycle of IVF in women - Milica Mitrović; Nikola Ćirović; Ivana Janković; Miljana Spasić Šnele; Jelena Opsenica Kostić; Mila Guberinić; Milan Trenkić (Health Psychology and Behavioral Medicine)
Introduction: Women typically experience more intense stress related to infertility compared to men, which is partly connected to the importance that motherhood and parenthood have for women in most societies. Considering the dominance of pronatalism in the majority of cultures, it is not surprising that women, who are most often considered responsible for reproduction, suffer greater social and psychological pressure due to infertility.Method: The study employs a social constructionist framework to explore how women facing infertility construct their notions of their first IVF treatment. Eleven women, aged 21–39, participated in the study and underwent semi-structured interviews. Thematic Analysis with a social constructionist epistemology was employed to investigate co-produced accounts of their first IVF.Results: Four ways of representing IVF emerged from the women’s statements about this procedure: IVF as a helpful step towards success; as a stressful journey into the unknown; as a game of chance; and as something I (do not) ask about.Discussion: The representations of IVF identified allow us to understand the subject positions of our participants that determine their thoughts, emotions, and behavior. In the narratives of almost all participants, we encounter different, even contradictory positions. The results allow us to understand better the needs of women facing infertility and to try to develop a system of treatment that is going to meet these needs, and therefore prevent the psychological consequences caused by this bio-psycho-social crisis.